Nutritional and health culture and its relationship to certain body components for football players under 20 years of age - Al-Hasnawi, L.Dr. Falah Hassan Alwan; Al-Wutaifi, L.Dr. Ashraf Abdul Amir Hadi; Al-Khashkhashi, L.Dr. Ahmed Radhi Kazem (Sulaimani Journal for Humanities, 2025)
This research aims to identify the nutritional and health culture and its relationship to certain body components of football players under 20 years of age. It also aims to study and understand healthy eating and its connection to the body composition of football players, as each component affects the players' performance level and helps them reach a high level through training and competition. This is the goal we are trying to achieve through a pilot study consisting of (12) players who were selected as the research population and not included in the main research experiment. The researcher used the descriptive approach with survey studies, as it was suitable for the nature of the research. The researcher selected the research sample purposively from players of Al-Kifl Sports Club and Al-Haydariya Sports Club in the junior and youth football categories. The sample size was (980) players, with a primary sample size of (860) individuals. The most important findings of the research were the existence of specific and clear objectives for nutritional and health awareness, and a correlation between the level of nutritional awareness and some body components of football players, excluding the athlete's dietary habits, nutritional supplements, and fat percentages. Similarly, a correlation was found between the level of health and some body components of football players, excluding the athlete's personal hygiene, periodic medical check-ups, and metabolic rate. The research concluded with the following: 1. The importance of increasing nutritional and health awareness among football players due to its clear impact on the athlete's health and, consequently, their performance during training and matches. 2. The use of a body composition measurement device, which is characterized by its ease and simplicity of use, to determine the athlete's body composition for evaluating and assessing training processes. 3. Activating the role of coaches as guides and mentors for athletes in following sound health and nutrition principles and their impact on body composition and overall health. Regular monitoring of athletes' health and consultation with a doctor in case of fatigue or deficiencies. 4. Encouraging clubs to provide balanced meals for athletes under the supervision of the team doctor or coach to maximize their nutritional benefits. Utilizing a nutritionist, given their crucial role in educating young athletes about nutrition, health, and their impact on performance. 5. Organizing regular lectures for athletes to enhance their health and nutritional awareness and promote healthy eating practices through expert guidance.
Keywords: Food culture; health culture